Cost of dialysis in Tanzania: Evidence from the provider's perspective - Lawrencia Mushi; Markus Krohn; Steffen Flessa (Health Economics Review, 2015)
Background: Although End Stage Renal Disease (ESRD) is a disease of increasing epidemiological relevance very little is known about the cost of providing the respective dialysis services in Tanzania. This paper estimates the costs of dialysis for ESRD patients at Muhimbili National Hospital (MNH) in Tanzania in the year 2014. Methods: Cost calculations are based on the provider perspective and include only the direct cost of dialysis treatment. Cost of drugs and consumables were obtained from the price list issued by the Medical Stores Department (MSD) in Tanzania. Additional data were collected through face-to-face interview with experts at the dialysis unit. Results: MNH performs on average 442 hemodialysis per month (34 patients, with three sessions per week) with a personnel placement of 20 nurses, four nephrologists, eight registrars, one nutritionist, two biomedical engineers, four health attendants and nine dialysis machines. The respective average unit cost per hemodialysis is 176 US. Consequently, an average patient requiring three dialyses per week (i.e. 156 dialyses per year) will cause annual costs of 27,440 US. Conclusion: The cost of dialysis is enormous for a least developed country like Tanzania where resources and technology are rather limited. Thus, from the economic point of view, it seems rational to allocate health care budgets towards diseases that are curable, have a higher cost-effectiveness and cater for the majority of the population. However, before a final decision on allocation of budgets towards dialysis is made all effort must be invested to improve technical efficiency by cutting the enormous unit cost.
Keywords: 330; Cost analysis; Hemodialysis; End-stage renal disease; Tanzania